Reactivity to Smoking Cues in a Social Context: Virtual Reality Experiment - Eidenmueller, Katharina; Hoffmann, Sabine; Kammler-Sücker, Kornelius; Wenger, Leonard; Mazza, Massimiliano; Mühle, Christiane; Stenger, Manuel; Meixner, Gerrit; Kiefer, Falk; Lenz, Bernd (JMIR Formative Research, 2025)
Background: Social contextual factors influence the onset and maintenance of substance abuse. Virtual reality (VR) provides a standardized method to present social stimuli and is increasingly used in addiction research. Objective: This study examines the influence of a smoking versus a nonsmoking agent in VR on craving in nicotine-dependent male participants. Our primary hypothesis was that the interaction with a smoking agent is associated with increased craving compared to a nonsmoking agent. We expected higher craving in the presence of an agent regardless of the agent’s smoking status. Methods: Using a head-mounted display (Oculus Rift), 50 nicotine-dependent smokers were exposed to four VR conditions on a virtual marketplace: first without an agent, second and third with an agent who either smoked or did not smoke in randomized order, and fourth without an agent as a follow-up condition. Before the follow-up condition, participants smoked a cigarette. Craving was assessed with the Questionnaire of Smoking Urges and a visual analog scale within VR and after each session. We also examined anxiety and agitation (visual analog scale), immersion and presence with the igroup Presence Questionnaire, and salivary cortisol levels. Results: Results showed no significant difference in the participants’ craving, anxiety, or agitation between the smoking and nonsmoking agent conditions. However, craving, anxiety, and agitation increased from the marketplace without an interacting agent to the conditions with an interacting agent, and decreased after smoking a cigarette. Immersion was low in all conditions and decreased over time. Salivary cortisol levels were highest at baseline and decreased over the course of the experiment. Conclusions: These findings suggest that the presence of an agent (as a contextual factor) may override the specific influence of proximal stimuli (burning cigarette). The low immersion highlights the challenges in developing effective VR environments for cue exposure.
CRIS-Team Scopus Importer:2025-06-06
Keywords: craving; cue reactivity; smoking; social context; virtual reality